The Effect of Using Storybird Application on Students’ Reading Comprehension of Narrative Text - Nisrina Nurdiani; Muhamad Sofian Hadi (Jurnal Studi Guru dan Pembelajaran, 2025)
The problem in this study is that many Indonesian students still face significant challenges in English reading comprehension, especially with narrative texts, which hinder their academic progress. Addressing this issue requires innovative pedagogical approaches utilizing technology. This research investigated the effect of the Storybird application in improving students’ reading comprehension of narrative text among ninth graders at SMP Negeri 3 Tangerang Selatan. A quantitative pre-experimental one-group pretest-posttest design was employed. The sample consisted of 47 ninth-grade students selected through convenience sampling. Data were collected using pre-test and post-test assessments and analyzed using descriptive statistics and a paired samples t-test. Data analysis revealed a significant increase in students’ scores, with an average improvement of 18.98 points between the pre-test (M=65.11) and post-test (M=84.09). The statistical calculation confirmed this difference was significant (t(46) = -16.492, p < 0.05). The study concluded that the Storybird application was effective as a teaching and learning medium for improving students’ reading comprehension of narrative text in this context.